Searching for Subversives : The Story of Italian Internment in Wartime America - Chopas, Mary Elizabeth Basile (Book collections on Project MUSE., 2017)
Shedding new light on an injustice often overshadowed by the mass confinement of Japanese Americans, Mary Elizabeth Basile Chopas traces how government and military leaders constructed wartime policies affecting Italian residents. Based on new archival research into the alien enemy hearings, this in-depth legal analysis illuminates a process not widely understood.